2009
DOI: 10.2147/opth.s4876
|View full text |Cite
|
Sign up to set email alerts
|

Overriding of the preseptal orbicularis oculi muscle in Caucasian cadavers

Abstract: We aimed to microscopically examine whether Caucasian eyelids demonstrate overriding of preseptal orbicularis oculi muscle (OOM) over the pretarsal OOM in both lower and upper eyelids. Full thickness sections of 13 lower eyelids and 11 upper eyelids from seven Caucasian cadavers were examined. In the lower eyelids, all 13 specimens demonstrated clear overriding of preseptal OOM over the pretarsal OOM. The overriding part extended almost to the level of lower eyelid margin. However, in the upper eyelids, only o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In our modified Wies technique, the rate of recurrence was 3.6% and the time to recurrence was 2 years in the sole patient who experienced recurrence. Another advantage of this method may be that recurrence occurs later than in other methods reported in the literature 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 . The cause of late recurrence may be fibrosis between the tarsus and retractors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our modified Wies technique, the rate of recurrence was 3.6% and the time to recurrence was 2 years in the sole patient who experienced recurrence. Another advantage of this method may be that recurrence occurs later than in other methods reported in the literature 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 . The cause of late recurrence may be fibrosis between the tarsus and retractors.…”
Section: Discussionmentioning
confidence: 99%
“…Involutional lower eyelid entropion is a frequently occurring malposition of the eyelid that may threaten the eyesight 3 . The main etiological factors are disinsertion or dehiscence of the lower eyelid retractors, vertical lid laxity secondary to dehiscence, lower eyelid laxity (either of the canthal tendons or of the eyelid itself), and overriding of the preseptal orbicularis over the pretarsal orbicularis 5 6 7 8 . An ideally effective technique would be able to correct all the causative factors, while minimizing the recurrence rate 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently, the role of hypertrophic orbicularis muscle was challenged by Kakizaki et al 18 They measured the orbicularis oculi muscle fiber diameter histologically and demonstrated that there was no significant difference in the average diameter of the muscle fibers between the patients with and without epiblepharon. 18 They concluded that there is no evidence of orbicularis oculi muscle hypertrophy in epiblepharon, and argued that orbicularis debulking does not treat the underlying etiology but merely helps in changing the direction of eyelashes. Based on the histological analysis, we devised a novel method of correcting the epiblepharon with resection of only skin.…”
Section: Discussionmentioning
confidence: 99%
“…The eyelid margin turns inward against the globe, causing tearing, irritation, foreign-body sensation, corneal ulcers, and subsequent vision loss. The aetiology is complex and includes horizontal lid laxity [1,2], vertical laxity resulting from lower eyelid retractor disinsertion or attenuation [3], and overriding of the preseptal orbicularis oculi muscle (OOM) [4]. To date, numerous surgical techniques have been reported, and those that addressed a single factor such as everting sutures (ES), and Jones, Wies, and lateral tarsal strip (LTS), have proven effective [5,6].…”
Section: Introductionmentioning
confidence: 99%